The End of the Cold War: Its Dynamics and Critical Factors - Ahmad Fuad Fanani (Jurnal Hubungan Internasional, 2015)
This essay will discuss the end of the Cold War and the critical factors which influenced its ending. It has been suggested that the Cold War actually was the ideological conflict between the Soviet Union and the United States. However, the conflict between the superpowers has triggered the military confrontation and security approach in the world after the end of the Second World War. As a result, many countries, especially the Third World countries became victims of the ideological rivalry between the United States and the Soviet Union.